Developments in the Alkynyltrifluoromethylations of Alkenes and Alkynes - Remete, Attila M.; Nonn, Melinda; Volk, Balázs; Kiss, Loránd (Synthesis, 2022)
As a consequence of the expanding relevance of fluorine-containing organic molecules in drug research, the synthesis of organofluorine scaffolds has high significance in synthetic organic chemistry. Trifluoromethylative difunctionalizations of carbon–carbon multiple bonds, with the simultaneous introduction of a CF3 group and another function, have considerable potential. Considering the high importance of carbon–carbon bond-forming reactions in organic synthesis, carbotrifluoromethylations and, in particular, alkynyltrifluoromethylations have increasing interest in synthetic chemistry. Alkynyltrifluoromethylation is a narrow area and a relatively new approach in synthetic chemistry; however it has not been reviewed so far. Our goal in this short review is to summarize recent developments in alkynyltrifluoromethylation reactions by considering: (a) alkynyltrifluoromethylation reactions of alkenes, including reactions involving either intramolecular alkynyl migration or intermolecular transformation, and (b) alkynyltrifluoromethylation reactions of alkynes.1 Introduction2 Alkynyltrifluoromethylation Reactions of Alkenes2.1 Reactions Involving Intramolecular Alkynyl Migration2.2 Intermolecular Reactions3 Alkynyltrifluoromethylation Reactions of Alkynes4 Summary and Outlook
Keywords: alkenes; difunctionalization; fluorine; photocatalysis; trifluoromethylation